"Don't buy this jacket": Consumer reaction toward anti-consumption apparel advertisement. Issue 4 (3rd October 2016) - Hwang, Chanmi; Lee, Youngji; Diddi, Sonali; Karpova, Elena
Abstract : Purpose: The purpose of this paper is to examine the effects of anti-consumption advertisement on consumers' attitudes and purchase intentions (PIs) of an apparel product. Design/methodology/approach: An experiment was conducted with a sample of college students ( n =1, 300) who were randomly assigned to view either a traditional advertisement for a Patagonia jacket or an anti-consumption advertisement of the same jacket. After that, consumer attitudes toward buying the jacket and PIs were measured employing online survey. In addition, consumer environmental concern (EC), perceived intrinsic brand motivation and extrinsic brand motivation (PIBM and PEBM) were measured to test a proposed research model. Findings: Participants exposed to the anti-consumption advertisement reported less positive attitudes toward and lower PIs to buy the jacket than participants who viewed the traditional advertisement. Participants' EC, PIBMs and PEBMs were found to be important predictors of the attitude and PI. Research limitations/implications: This study provides a foundation for future research on consumer attitudes and PIs in the context of anti-consumption behavior and the effects of anti-consumption advertisement. Limitations of the present study include convenience sampling. Practical implications: Anti-consumption advertising might be used effectively to raise consumers' awareness on their spending habits on clothing and reduce the clutter of consuming culture. Originality/value: The research findings contribute to the corporate social responsibility literature in the apparel context, specifically socially responsible marketing, by focusing on the nascent topic of anti-consumption. This was the first study that examined how anti-consumption advertisement might affect consumer attitudes toward buying products displayed in this advertisement.